Answer:
9
Explanation:
To find the value of the expression "6x - 9", we would first need to find the value of "x" and then replace and solve.
The equation we are given is:
4x + 15 = 27
We can solve this by taking the numbers to one side and solving for the variable "x", shown below:
![4x + 15 = 27\\4x=27-15\\4x=12\\x=(12)/(4)\\x=3](https://img.qammunity.org/2020/formulas/mathematics/high-school/xjfh24amfxw6da0scj7vxkuf7ru6ry31wb.png)
Now we replace "x" with "3" in the expression:
6x - 9
= 6(3) - 9
= 18 - 9
= 9